Sentinel lymph node biopsy and morbidity outcomes in early cervical cancer: Results of a multicentre randomised trial (SENTICOL-2). (May 2021) - Mathevet, Patrice; Lécuru, Fabrice; Uzan, Catherine; Boutitie, Florent; Magaud, Laurent; Guyon, Frederic; Querleu, Denis; Fourchotte, Virginie; Baron, Marc; Bats, Anne-Sophie; Morice, P.; et al.
Abstract: Introduction: Pelvic lymph node dissection has been the standard of care for patients with early cervical cancer. Sentinel node (SN) mapping is safe and feasible and may increase the detection of metastatic disease, but benefits of omitting pelvic lymph node dissection in terms of decreased morbidity have not been demonstrated. Materials and methods: In an open-label study, patients with early cervical carcinoma (FIGO 2009 stage IA2 to IIA1) were randomly assigned to SN resection alone (SN arm) or SN and pelvic lymph node dissection (SN + PLND arm). SN resection was followed by radical surgery of the tumour (radical hysterectomy or radical trachelectomy). The primary end-point was morbidity related to the lymph node dissection; 3-year recurrence-free survival was a secondary end-point. Results: A total of 206 patients were eligible and randomly assigned to the SN arm (105 patients) or SN + PLND arm (101 patients). Most patients had stage IB1 lesion (87.4%). No false-negative case was observed in SN + PLND arm. Lymphatic morbidity was significantly lower in the SN arm (31.4%) than in the SN + PLND arm (51.5%; p = 0.0046), as was the rate of postoperative neurological symptoms (7.8% vs. 20.6%, p = 0.01, respectively). However, there was no significant difference in the proportion of patients with significant lymphoedema between the two groups. During the 6-month postoperative period, the difference in morbidity decreased over time. The 3-year recurrence-free survival was not significantly different (92.0% in SN arm and 94.4% in SN + PLND arm). Conclusion: SN resection alone is associated with early decreased lymphatic morbidity when compared with SN + PLND in early cervical cancer. Highlights: Randomised study comparing sentinel node biopsy and pelvic lymph node dissection. Sentinel node biopsy alone is associated with decreased minor lymphatic morbidity. No increased risk of recurrence while omitting pelvic lymph node dissection.